The Impact of Critical Illness on the Outcomes of Cardiac Surgery in Patients with Acute Infective Endocarditis - Mbakise P. Matebele; Kanthi R. Vemuri; John F. Sedgwick; Lachlan Marshall; Robert Horvath; Nchafatso G. Obonyo; Mahesh Ramanan (Hearts)
Background: This study aims to evaluate the impact of critical illness, defined as the need for preoperative intensive care unit (ICU) admission for invasive monitoring or organ support, on cardiac surgery outcomes for patients with acute infective endocarditis (IE). Methods: A retrospective analysis of prospectively collected data from patients treated between 1 January 2017 and 30 May 2024 at a single Australian tertiary cardiothoracic centre was performed. Data were collected from the Australian and New Zealand Cardiothoracic Society (ANZCTS) database and the Australian and New Zealand Intensive Care Adult Patients Database (ANZICS-APD). Results: Among 342 patients who underwent cardiac surgery for IE, 32 (9.4%) were critically ill. The critically ill patients were admitted to the ICU before surgery with a diagnosis of septic or cardiogenic shock, with 86% (n = 30) requiring mechanical ventilation. Compared to the non-critically ill cohort, critically ill patients were more likely to have a history of intravenous drug use (IVDU) (41% vs. 14%, p = 0.03) and a younger age (median age 49 years [42–56] vs. 61 years [44–70], p = 0.03), and although methicillin-sensitive Staphylococcus aureus (MSSA) was the most common causative organism in both groups, it was found significantly more often in the critically ill cohort (66% and 27%, p = 0.001). The median EuroSCORE II was comparable between the groups (2.1 [1.3–10] vs. 2.8 [1.3–5.7], p = 0.69); however, the APACHE III (57 [49–78] vs. 52 [39–67], p = 0.03) and ANZROD scores (0.04 [0.02–0.09] vs. 0.013 [0.004–0.038], p = 0.00002) were significantly higher in the critically ill patients. The overall 30-day mortality rates were similar between the groups (13% vs. 5%, p = 0.60). The median ICU length of stay (LOS) was significantly longer for the critically ill patients (5 days [IQR 2–10 days] vs. 2 days [1–4 days], p = 0.0004), with a similar hospital LOS (23 days [IQR 14–36] vs. 21 days [12–34], p = 0.46). Renal replacement therapy was three times higher in the critically ill (34% vs. 11%, p = 0.0001). Reoperations for bleeding were similar between the groups (16% vs. 11%, p = 0.74). Conclusions: Despite being associated with higher ANZROD and APACHE III scores, a longer ICU length of stay, and higher use of renal replacement therapy, critical illness did not have an impact on the EuroSCORE II, hospital length of stay, or reoperation rates for bleeding or 30-day mortality among patients with IE undergoing cardiac surgery. The lessons from this study will guide and inform the development of better infective endocarditis databases and registries.